Atypical radiological presentation of fatal invasive cerebral aspergillosis in a patient with acute lymphoblastic leukemia after allogeneic bone marrow transplant: A case report - Weronika Machaj; Adrian Korbecki; Wiktoria Bińczyk; Bartosz Siudek; Marek Ussowicz; Anna Zimny (Radiology Case Reports)
Invasive aspergillosis is a severe fungal infection that primarily affects individuals with weakened immune systems. This report presents the case of a 20-year-old male diagnosed with acute lymphoblastic leukemia who developed invasive aspergillosis following an allogeneic hematopoietic stem cell transplant. Despite aggressive antifungal treatment, the infection progressed to the central nervous system, ultimately leading to the patient’s death. This case highlights the challenges associated with diagnosis and treatment of invasive aspergillosis in immunocompromised individuals and underscores the need for advancements in both diagnostic techniques and therapeutic strategies.